2010
DOI: 10.4103/0972-5229.63029
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Sepsis Guidelines: summary for resource-limited countries

Abstract: Justification:Pediatric sepsis is a commonly encountered global issue. Existing guidelines for sepsis seem to be applicable to the developed countries, and only few articles are published regarding application of these guidelines in the developing countries, especially in resource-limited countries such as India and Africa.Process:An expert representative panel drawn from all over India, under aegis of Intensive Care Chapter of Indian Academy of Pediatrics (IAP) met to discuss and draw guidelines for clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…This is consistent with previous research in similar settings [11, 3234]. For example, a survey of Rwandan district hospitals identified limited availability of resources necessary to provide neonatal and pediatric emergency care (e.g., all hospitals surveyed lacked intra-osseous needles for the management of shock and half of the hospitals evaluated lacked BVM for newborns) [34].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with previous research in similar settings [11, 3234]. For example, a survey of Rwandan district hospitals identified limited availability of resources necessary to provide neonatal and pediatric emergency care (e.g., all hospitals surveyed lacked intra-osseous needles for the management of shock and half of the hospitals evaluated lacked BVM for newborns) [34].…”
Section: Discussionsupporting
confidence: 86%
“…In Kenya, English and colleagues found that many essential items for the care of severely ill children were lacking in many district hospitals [33]. Likewise, shortages of drugs, equipment, disposable materials as well as facilities made it difficult to implement sepsis management guidelines in Mongolia [32]. While in the ETAT+ training healthcare workers are taught how to correctly assess children with dehydration/shock and how to resuscitate them with fluid, including putting an intra-osseous (IO) line when necessary, our findings and prior research suggest that some of the required equipment are not available in the hospitals and this may therefore hamper successful implementation of the ETAT+ program in Rwanda [34].…”
Section: Discussionmentioning
confidence: 99%
“…[11] Children who had PICU stay of <6 h, trauma patients, surgical patients, patients transferred from other center were excluded from the study. Children who left against medical advice whose final outcome could not be ascertained were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were managed as per standard clinical guidelines for management of sepsis in children. [11] The management includes placement of central venous catheter, appropriate fluid resuscitation, use of inotropes, empirical antibiotics, and blood component transfusion.…”
Section: Methodsmentioning
confidence: 99%
“…The objectives of these recommendations were to standardize patient care and further reduce mortality and morbidity in pediatric sepsis. These guidelines represent best clinical practice; however, stronger evidence is lacking to confirm the components of these recommendations; almost all levels of references and recommendations in pediatric septic shock treatment are low [6-8]. …”
Section: Introductionmentioning
confidence: 99%